2023
DOI: 10.1111/jan.15605
|View full text |Cite
|
Sign up to set email alerts
|

Embedding nurse‐led supportive care in an outpatient service for patients with Chronic Obstructive Pulmonary Disease

Abstract: AimTo describe a small multidisciplinary team's experience of the process of embedding nurse‐led supportive care into an existing Chronic Obstructive Pulmonary Disease outpatient service.DesignCase study methodologyMethodsData were collected from multiple sources including key documents and semi‐structured interviews with healthcare professionals (n = 6) conducted between June and July 2021. A purposive sampling strategy was used. Content analysis was applied to key documents. Interviews were transcribed verba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Interdisciplinary collaboration, nested in shared responsibility for patient‐family welfare guidance of patients for services in the healthcare and social system, is essential in partnership‐based nursing practice. The significance of the role of nurses as leaders in such collaboration in chronic care is noteworthy (Ora et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interdisciplinary collaboration, nested in shared responsibility for patient‐family welfare guidance of patients for services in the healthcare and social system, is essential in partnership‐based nursing practice. The significance of the role of nurses as leaders in such collaboration in chronic care is noteworthy (Ora et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A synthesis of approaches is needed to maximize proper symptom management and to account for the complex and deep-seated existential, psychological and social issues that people with COPD and their families face (Iyer et al, 2019;Ora et al, 2023). Vermylen et al (2015) suggested a model, Proactive palliative care in COPD, that highlights ongoing communication with patients, incorporating advanced care planning, 'meaning-centred care' and collaboration as appropriate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2018 and 2020, nurse‐led supportive care was embedded in an existing nurse‐led COPD outpatient model of care through a collaboration between respiratory and palliative care services in a tertiary hospital in Sydney, Australia (Ora et al., 2023). Nurse‐led COPD supportive care was introduced into the COPD service to better address the biopsychosocial‐spiritual needs of patients with COPD and to enhance the respiratory team's primary palliative care skills.…”
Section: Methodsmentioning
confidence: 99%
“…Supportive care is therefore distinguished as an approach that may be more appropriate for patients living with COPD, than current palliative care models that tend to cater best to patients with more predicable patterns of decline and relatively short‐term care needs such as patients with advanced cancer (Luckett et al., 2014). The authors have previously published the nurse‐led model of supportive care that was embedded into an existing COPD outpatient service (Ora et al., 2023). This paper reports on an evaluation of a nurse‐led model of COPD supportive care from patient and caregiver perspectives.…”
Section: Introductionmentioning
confidence: 99%